Development of Comic-Based Arabic Language Learning Materials for Students at Islamic Junior High School, Medan: Implementation of the ADDIE R&D Model - Lia Harahap; Erka Pulungan; Aidil 'Azza Mu'izzuddin; Hakmi Wahyudi (Universitas Islam Negeri Palopo, 2026)
Arabic language learning at lower secondary school level often faces various challenges, such as low student motivation and a lack of engaging and innovative teaching materials. Although a number of studies have examined the use of visual media in language learning, few have systematically developed illustrated comic books specifically for Arabic language learning at Islamic lower secondary schools within the context of local Indonesian culture this gap forms the basis of this research. This study aims to develop illustrated comic-based Arabic language learning materials for Year 8 students at Al-Ulum Terpadu Islamic Junior High School in Medan using the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observation, interviews, validation questionnaires, and learning outcome tests. The results of the subject matter expert validation showed a feasibility percentage of 87.5%, whilst the media expert validation yielded 85.0%; both fell within the ‘highly feasible’ category. The pilot test with students yielded an average positive response score of 88.3%, with a learning gain (N-Gain) of 0.62, which falls within the moderate-to-high category. Unlike Arabic language learning materials, which are generally text-based, the illustrated comic media developed in this study integrates contextual visual narratives with vocabulary and dialogue content in a cohesive manner, thereby making a tangible contribution to the innovation of Arabic language learning materials in Islamic secondary schools.